Oral and Nasal Vowels in Pontianak Teochew - Veniranda, Yohana (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
The purpose of the study is to analyze the acoustic properties of the oral and nasal vowels, in terms of the values of the formants, the fundamental frequencies, the anti-formants, the intensity, and the bandwidths. The data were recorded and analyzed using the Praat program. The results show that there are changes of the average values of all the properties. The fundamental frequencies of the nasal vowels are all higher than their counterpart oral vowels. The hypothesis is correct for this acoustic property. However, by the test of significance t-test, only the nasal [a?] and diphthong [u?a?] have significantly higher frequencies. The results of the average of intensity show that nasal vowels/ diphthongs may not always have higher intensity than their counterpart oral vowels/ diphthongs.